Computational Investigation of the Aza-Cope Rearrangement Leading to Angularly Substituted 1-Azabicyclic Rings - Meyrelles, Ricardo; Fetisleam, Yener; Maryasin, Boris (Synlett, 2022)
A computational study of the aza-Cope rearrangement leading to angularly substituted 1-azabicyclic ring systems is presented. The calculations estimate the probability of the proton transfer between reaction intermediates and protic solvents, explain the experimentally observed reaction selectivity, and suggest new potentially more efficient systems for further in vitro and in silico investigations.
Keywords: aza-Cope rearrangement; DFT; reaction mechanisms; sigmatropic rearrangements; proton transfer; cis–trans selectivity